Shining Light on Atmospherics: How Ambient Light Influences Food Choices - Biswas, Dipayan; Szocs, Courtney; Chacko, Roger; Wansink, Brian (Journal of Marketing Research, 2017)
Retail atmospherics is emerging as a major competitive tool, and it is especially notable in the restaurant industry, where lighting is used to create the overall ambience and influence consumer experience. In addition to influencing overall experience, can ambient light luminance have unintended consequences in terms of influencing what diners order? The results of a field study at multiple locations of a major restaurant chain and a series of lab studies robustly show that consumers tend to choose less healthy food options when ambient lighting is dim (vs. bright). Process evidence suggests that this phenomenon occurs because ambient light luminance influences mental alertness, which in turn influences food choices. While restaurant and grocery store managers can use these insights and their ambient light switches to nudge consumers toward targeted food choices, such as healthy or high-margin signature items, health-conscious consumers can opt for dining environments with bright ambient lighting.